Antioxidant and Anticancer Activities of Methanol Extract of Seeds of Datura stramonium l. - Iqbal, Saleem; Sivaraj, Chandrasekaran; Gunasekaran, Krishnasamy (Free Radicals and Antioxidants)
Background: Datura stramonium belongs to the family Solanaceae which is commonly dubbed as thorn apple or jimson weed, and is abundant throughout tropical and subtropical regions. Datura seeds and leaves are used as anti-asthmatic, antispasmodic, hypnotic and narcotic. Externally, the jimson seeds are used in treating fistulas and abscesses. It has been used by the British soldiers to treat respiratory problems. Datura has also finds its utility in Ayurveda for asthma symptoms where jimson weed’s leaves are smoked in cigarette or pipe. Objectives: Aim of the present study was to investigate the antioxidant and antiproliferative activities of methanol extract of seeds of D. stramonium. Materials and Methods: Antioxidant assays such as DPPH˙ radical, superoxide radical, ABTS˙+ radical cation, OH˙ radical scavenging assays, Phoshomolybdenum reduction and Fe3+ reducing power assays were investigated. Thin layer chromatography was performed to find out compounds present in the methanol extract. in vitro cytotoxic activity for MCF7 (breast cancer) cell line was too studied by MTT reagent assay method. Results: IC50 values of DPPH˙ radical, superoxide radical, ABTS˙+ radical cation, OH˙ radical scavenging assays were 35.26, 10.50, 49.36 μg/mL concentration respectively. TLC analysis showed the presence of compounds with Rf values of 0.76 and 0.58 in the methanol extract of D. stramonium. Cytotoxic activity for MCF7 cell line was 66.84% at 500 μg/mL concentration of methanol extract. Conclusion: Here Current study corroborates that D. stramonium is enriched with fine source of significant natural oxidants with anticancer agents and has therapeutic potential for treatment of diseases, induced by oxidative stress, Further research work is required to isolate active compounds for clinical trials.
Keywords: Datura; Antioxidant; Cytotoxicity; MCF7 cell line; MTT assay